(untitled) (International Seven Journal of Health Research, 2025)
Spirulina (Arthrospira platensis) is a blue-green cyanobacterium that grows in fresh and salt water. It is known to be a rich source of nutrients, including proteins, vitamins, minerals, and antioxidants. One of its main applications is its use as nutritional supplement, where Spirulina is often consumed to its high protein content and other essential nutrients. It is especially popular among vegetarians and vegans due to its complete protein quality. Some studies suggest that Spirulina may have several health benefits, such as reducing cholesterol, controlling blood pressure, strengthening the immune system and protecting against cardiovascular diseases. It has also been reported to act as a detox agent, since Spirulina is known for its ability to detoxify the body, helping to remove heavy metals and toxins from the body. In the cosmetics field, due to its antioxidant and nourishing properties, Spirulina is used in several products, such as facial creams, hair masks, and body lotions to promote skin and hair health. It is also used in agriculture as an organic fertilizer and in animal feeding, especially in aquaculture, as a source of protein for fish and shrimp. In summary, Spirulina is a valuable source of nutrients and has a variety of applications, from nutritional supplements to cosmetics and agriculture. Its health benefits and potential for sustainable use make it a popular choice in many areas. Therefore, in this article we review the applications of Spirulina (Arthrospira platensis).